2007
DOI: 10.1007/s00284-006-0491-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mycoplasmas on Apoptosis of 32D Cells Is Species-Dependent

Abstract: We previously showed that mycoplasmal infection effectively prevented apoptosis of infected cells, whereas other researchers have indicated that mycoplasmal infection promoted apoptosis. To understand the mechanism underlying this discrepancy, five different species of mycoplasmas were investigated for their effects on apoptosis of interleukin (IL)-3-dependent 32D cells. Results revealed that Mycoplasma fermentans and M. penetrans effectively supported continuous growth of 32D cells after IL-3 withdrawal. M. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In contrast, M. hominis and Mycoplasma salivarium accelerated apoptosis of 32D cells and M. genitalium had no significant effect on apoptosis. The authors of the cited work suggested that different species of mycoplasma can modify the expression of key regulatory genes of apoptosis in different ways and therefore may have either a pro‐ or an antiapoptotic effect (S. Zhang & Lo, ). The molecular nature of the differences between species of mycoplasmas in their ability to modulate signaling one way or another is still not clear.…”
Section: Mycoplasma Infections and Inflammationmentioning
confidence: 99%
“…In contrast, M. hominis and Mycoplasma salivarium accelerated apoptosis of 32D cells and M. genitalium had no significant effect on apoptosis. The authors of the cited work suggested that different species of mycoplasma can modify the expression of key regulatory genes of apoptosis in different ways and therefore may have either a pro‐ or an antiapoptotic effect (S. Zhang & Lo, ). The molecular nature of the differences between species of mycoplasmas in their ability to modulate signaling one way or another is still not clear.…”
Section: Mycoplasma Infections and Inflammationmentioning
confidence: 99%
“…Thus, they suggested that M hominis, M genitalium infections do not play any major role in cervical carcinoma development (Biernat-Sudolska et al, 2011). At least there are two studies related to the M genitalium effects on apoptosis, in one of them, the data did not show any significant effect on apoptosis in M genitalium-infected 32D (a murine myeloid cell) cell line (Zhang and Lo, 2007). In contrast, the other one indicated M genitalium can inhibit apoptosis in 32D cell line (Feng et al, 1999).…”
Section: Cancer Associationsmentioning
confidence: 99%
“…Mycoplasma species are known for their apoptosis-modulating effects on host cells. However, these vary from apoptosis induction [25, 26] to inhibition of cell death [27, 28], indicating that additional research should be made to clarify these data.…”
Section: Discussionmentioning
confidence: 99%